PENGEMBANGAN MODUL DESAIN BUSANA DENGAN ADOBE PHOTOSHOP CS3 - Arni, Handri; Efi, Agusti; Rahmiati, Rahmiati (Journal of Home Economics and Tourism, 2012)
The aim of this research is to design and make colouring technic fashiondesign with Adobe Photoshop CS3 as the alternative of learning media and able to beused to give some helps in explain the materials in class or personally. The researchuse research and development method, which is designing an make a module ofcolouring fashion design with Adobe Photoshop CS3. Data collection in this researchuse validation and gave to the lectures and the questionnaire to the students about themodule. The questionnaire consists of form, contents, motivation and the practicalityof this module. Data analyzed using Likert Scale. Hoped this module can give theeasiness for the lecturer and other people in designing a learning media, so canmotivate the student, and the aim of the learning is gained.